Beckman DSA-560, Sample Handling Tray - Beckman Instruments Photographic Services Section (1968)
The DSA-560 Discrete Sample Analyzer, introduced in 1968, was Beckman's first clinical chemistry analyzer. It was capable of processing 100 samples per hour and used in the analysis of blood serum, urine, and drinking water.
Keywords: Scientific apparatus and instruments; Clinical chemistry--Instruments; Beckman Instruments, Inc.